PENGARUH GAYA KEPEMIMPINAN, MOTIVASI, PRODUKTIVITAS KERJA TERHADAP KINERJA KARYAWAN PT. ISS INDONESIA - Superman; Hazriyanto (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
The purpose of this study is to determine the leadership style, motivation, as an indicator of work productivity which is responded to by the performance of employees at PT. ISS Indonesia Batam Branch. This study took a sample of 195 respondents. The data source is primary data with data collection methods using a linkert scale questionnaire. By using simple random sampling to find out the responses of respondents about each - each variable. The data analysis technique used is descriptive analysis and part analiysis. The results of the path analysis show that leadership style on work productivity, motivation on work productivity, motivation on employee performance and productivity on employee performance have a significant effect because the t-statistic value is above the t-table (t-table with a significance of 5% and DF = 157 is 1.975189). The results of testing the coefficient of leadership style parameters to work productivity are 0.5698, motivation to work productivity is 0.3989, motivation to employee performance is 0.4662 and work productivity to employee performance is 0.4950.